Patterns and drivers of forest land cover changes in tropical semi-deciduous forests in Ghana. Issue 1 (2nd January 2017) - Addo-Fordjour, Patrick; Ankomah, Frank
ABSTRACT: This study was conducted to determine the patterns and drivers of forest land cover changes in Bobiri and Oboyow Forest Reserves (BFR and OFR, respectively), Ghana. Landsat images were employed to determine forest land cover types and changes in 1990, 2000 and 2010 using supervised classification method. Factors that drive forest land cover changes in the forest reserves were determined using a semi-structured questionnaire and field observations. Generally, closed-canopy forest decreased by 49% in both forests over 20-year period resulting in a tremendous increase in open-canopy forest (BFR: 85%; OFR: 46%) and non-forest land cover types (BFR: 48–80% OFR: 127–350%). Factors such as logging manual illiteracy among timber operators, offences of authorised timber operators, ineffective community participation, harvesting schedule revision, chainsaw logging, illegal logging, bushfires, fuel gathering and weak penalty for offences were identified as contributing to rapid depletion of closed canopy forest cover in the forest reserves.